Comparison of Photopic Negative Response of Full-Field and Focal Electroretinograms in Detecting Glaucomatous Eyes. (30th September 2010) - Machida, Shigeki; Tamada, Kunifusa; Oikawa, Taku; Gotoh, Yasutaka; Nishimura, Tomoharu; Kaneko, Muneyoshi; Kurosaka, Daijiro
Abstract : Purpose . To compare the photopic negative response (PhNR) of the full-field electroretinogram (ERG) to the PhNR of the focal ERGs in detecting glaucoma. Methods . One hundred and three eyes with glaucoma and 42 normal eyes were studied. Full-field ERGs were elicited by red stimuli on a blue background. The focal ERGs were elicited by a 15 ∘ white stimulus spot centered on the macula, the superotemporal or the inferotemporal areas of the macula. Results . In early glaucoma, the areas under the receiver operating characteristic curves (AUCs) were significantly larger for the focal PhNR (0.863–0.924) than those for the full-field PhNR (0.666–0.748) (P < .05 ). The sensitivity was significantly higher for the focal PhNR than for the full-field PhNR in early (P < .01 ) and intermediate glaucoma (P < .05 ). In advanced glaucoma, there was no difference in the AUCs and sensitivities between the focal and full-field PhNRs. Conclusions . The focal ERG has the diagnostic ability with higher sensitivity in detecting early and intermediate glaucoma than the full-field ERG.